Introduction of Sunflower Number Media to Enhance Symbolic Thinking Ability in Early Childhood - Halifah, Syarifah; Palintan, Andi Tien Asmara; Nadia, Nadia; Rading, Astira; Tadzkirah, Tadzkirah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
This research aims to introduce the sunflower media numbers in enhancing the development of symbolic thinking in early childhood. This research involves various aspects of child development, including moral and religious values, cognitive, and language. The research methodology uses a qualitative descriptive approach with the subjects of 17 children. Data collection techniques use observations and interviews to find out the processes of sunflower media numbers in enhancing symbolic thinking in children. The results of the research show that the application of sunflower media numbers can increase the enthusiasm of children in solving problems by arranging the numbers according to the solar pattern. Overall, the average indicator of symbolic thinking development indicates a continuous improvement, with children aged 5-6 years in the category of starting to develop (NA), developing as expected (MF), and developing very well (SA). Based on these findings, it can be concluded that the application of the sunflower media figures achieved as expected in improving the child's ability to think symbolically.